Shaping Future Generation Through Innovative Methods of Teaching - Kaur, Manpreet (PT FORMOSA CENDEKIA GLOBAL, 2024)
Innovation in education is the index of development and teacher is the facilitator in this globalize world. Teachers of today's world have to meet the needs of the present education system without compromising the ability of future generation. Educational technology has given birth to